Antihistamines and Febrile Seizure Susceptibility - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Charts of children with febrile seizures admitted to the Hospital of Shiga University of Medical Sciences, Otsu, Japan, 2006-2007, were reviewed retrospectively.